EVALUATION OF THE ROLE OF APPLICATION OF CONTACT LITHOTRIPSY IN LARGE OCCLUSING URETERAL STONES - Ivashchenko, D.M.; Dudchenko, M.O.; Kravtsiv, M.I. (World of Medicine and Biology, 2020)
The study was devoted to the analysis of the effectiveness of contact lithotripsy and its comparison with the effectiveness of extracorporeal lithotripsy in patients with large (> 10 mm) ureteral calculi, accompanied by urinary tract obstruction. We also analyzed a group of patients who underwent lithotripsy in 2 surgical stages with preliminary stenting of the urinary tract. According to the results of the study, a shorter duration of pain syndrome and hematuria was noted in patients who underwent contact lithotripsy and achieved “stone free” state, compared with distance lithotripsy. When comparing the group's indicators with preliminary stenting of the ureters, it was noted that the duration of hematuria was shorter on average by 12%, pain syndrome was shorter on average by 16%. So, contact lithotripsy as a method of management of large urinary tract stones can be recommended as a 1st level therapy in the absence of contraindications to surgical treatment.
Keywords: Contact lithotripsy; ureteral calculi; renal colic